EzyAgric app for input quality tracing for Ugandan smallholder farmers - Ajambo, Susan; Ochieng, S.; Kikulwe, Enoch; Abucheli, Eliud (CGIAR System Organization, 2024)
The EzyAgric app provides smallholder farmers with an integrated service platform to support farm management and good agricultural practices, and access to agri-inputs and credit in Uganda.